Silica Modified Natural Dye of Caesalpinnia sappan l. on Cotton Fabrics - Kun Sri Budiasih; Eli Rohaeti; Isti Yunita; Azlan Kamari (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
Sappana (Caesalpinnia sappan L.) has been known as a natural dye in textiles and food. This research aimed to develop a sappan-based natural dye for fabrics dyeing by SiO2 modification as the UV protection agent. The sappan dye and its color were measured by colorimetric methods on UV-Vis spectrophotometry. The testing of the material includes a standard color detection test on the solution and washing resistance on cotton fabrics. The product is the prototype of a stable natural dye product of SiO2 modified - sappan (Si-Cs) which will be performed consistently on cotton fabrics. The result showed that SiO2-modified sappan dye had a higher absorbance in UV-Vis Spectrometer. The performance of the coloring product was also better than the standard sappan dye, indicated by the higher Ultraviolet Protection Factor and the fastness value. Variations of coloring products affected by the mordant agents varied from orange-red-purple caused by non-mordant–alum acetate and iron mordant respectively.